Harmonization of the All-European Standards for the Border Guards Training: Ukrainian Experience - Balendr, Andrii (Pedagogical Discourse, 2019)
The article reveals the peculiarities of implementation of the Sectoral Qualification Framework the border protection sphere of the European Union (EU) countries and the role of the State Border Guard Service of Ukraine (SBGSU) in this process, in order to use the experience gained to further integrate the SBGSU into the system of unified professional training of the personnel of the border guard authorities of the EU countries. The organization of validation of the sectoral qualification framework for the preparation of border guards of the EU countries has been considered. The special attention has been payed to the procedure of checking the validity of the Sectoral Qualification Framework, which included a set of measures: inspection by representatives of EU countries; consultations with partner organizations; verification and revision; introduction and harmonization of the mechanism of quality assurance of the Sectoral Qualification Framework. The Border Guard Service of Ukraine, in cooperation with the FRONTEX Agency in 2016 actively joined the process of implementation of the updated Sectoral Qualification Framework for border guards training as FRONTEX partner country. It has been concluded that for the organization of the system of effective preparation of border guards of Ukraine and its adaptation to the requirements of the leading EU countries, it is necessary to study more deeply the issue of the implementation of the Sectoral Qualifications Framework for the preparation of border guards of the EU countries, which requires studying the problem of validation of the qualification framework. The author indicates that the system of training of the personnel of the State Border Guard Service of Ukraine requires such an instrument for development of national border guard competencies, and that presupposes further study of the border guard’s training system of the EU countries.